THE INFLUENCE OF SCHOOL CULTURE, LEARNING INTEREST, AND LEARNING MOTIVATION ON SCIENCE LEARNING OUTCOMES - Gusti Ayu Agung Purnadewi; Nengah Arnawa; Sri Tatminingsih (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to determine the effect of school culture, interest in learning, and learning motivation on science learning outcomes for fifth grade elementary school students in cluster IV, Tabanan sub-district in 2022. This research is an ex post-facto research. The population in this study were 402 students, while the research sample used was 196 students. Determination of the sample is done by random sampling technique. The data collection method used in this research is the questionnaire method and document study. Data on school culture, learning interests, and learning motivation were collected using the questionnaire method, while data on students' natural science learning outcomes were collected using the document study method. The data analysis used in this study is multiple regression and partial correlation. Based on the research that has been done, it is concluded that: 1) there is a significant influence of school culture on science learning outcomes, with an effect of 42.1% and an effective contribution of 20.7%. 2) There is a significant effect of interest in learning on science learning outcomes, with an effect of 44.4% and an effective contribution of 18.5%. 3) There is a significant effect of learning motivation on science learning outcomes, with an effect of 44.1% and an effective contribution of 17%. And 4) Taken together, there is a significant influence of school culture, learning interest, and learning motivation on science learning outcomes, with an effect of 56.2%. 1% and an effective contribution of 20.7%. 2) There is a significant effect of interest in learning on science learning outcomes, with an effect of 44.4% and an effective contribution of 18.5%. 3) There is a significant effect of learning motivation on science learning outcomes, with an effect of 44.1% and an effective contribution of 17%. And 4) Taken together, there is a significant influence of school culture, learning interest, and learning motivation on science learning outcomes, with an effect of 56.2%. 1% and an effective contribution of 20.7%. 2) There is a significant effect of interest in learning on science learning outcomes, with an effect of 44.4% and an effective contribution of 18.5%. 3) There is a significant effect of learning motivation on science learning outcomes, with an effect of 44.1% and an effective contribution of 17%. And 4) Taken together, there is a significant influence of school culture, learning interest, and learning motivation on science learning outcomes, with an effect of 56.2%.